2014
DOI: 10.1371/journal.pone.0104363
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Repeat Polymorphism in the MITF-M Promoter Is a Key Regulator of White Spotting in Dogs

Abstract: The white spotting locus (S) in dogs is colocalized with the MITF (microphtalmia-associated transcription factor) gene. The phenotypic effects of the four S alleles range from solid colour (S) to extreme white spotting (sw). We have investigated four candidate mutations associated with the sw allele, a SINE insertion, a SNP at a conserved site and a simple repeat polymorphism all associated with the MITF-M promoter as well as a 12 base pair deletion in exon 1B. The variants associated with white spotting at al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 28 publications
(43 reference statements)
2
59
0
1
Order By: Relevance
“…Subsequent functional studies revealed that regulatory mutations located in the MITF‐ M promoter influenced transcription where a simple repeat polymorphism was shown to be a key factor underlying white spotting (Baranowska Körberg et al . 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Subsequent functional studies revealed that regulatory mutations located in the MITF‐ M promoter influenced transcription where a simple repeat polymorphism was shown to be a key factor underlying white spotting (Baranowska Körberg et al . 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Given that Mitf is evolutionarily conserved, it is not surprising that its roles in pigmentation can be seen in other species. In domestic dogs (Baranowska Körberg et al 2014) and horses (Hauswirth et al 2012), for instance, alterations in the promoter giving rise to the major melanocyte isoform of MITF are responsible for white spotting. Nevertheless, pigmentation need not always be the major target for Mitf homologs.…”
Section: Microphthalmia-associated Transcription Factor (Mitf) Geneticsmentioning
confidence: 99%
“…The Dalmatians spots are another trait fixed in the breed. One gene responsible for this phenotype is MITF, which causes the extreme white spotting [24,25]. The colored spots result from the influence of a ticking locus [25].…”
Section: Analysis Of Genes Located In Consensus Rohsmentioning
confidence: 99%